Vascular smooth muscle cell proliferation as a therapeutic target. Part 1: molecular targets and pathways - Wang, Dongdong; Uhrin, Pavel; Mocan, Andrei; Waltenberger, Birgit; Breuss, Johannes M.; Tewari, Devesh; Mihaly-Bison, Judit; Huminiecki, Łukasz; Starzyński, Rafał R.; Tzvetkov, Nikolay T.; Horbańczuk, Jarosław; Atanasov, Atanas G. (Biotechnology advances, 2018)
Cardiovascular diseases are a major cause of human death worldwide. Excessive proliferation of vascular smooth muscle cells contributes to the etiology of such diseases, including atherosclerosis, restenosis, and pulmonary hypertension. The control of vascular cell proliferation is complex and encompasses interactions of many regulatory molecules and signaling pathways. Herein, we recapitulated the importance of signaling cascades relevant for the regulation of vascular cell proliferation. Detailed understanding of the mechanism underlying this process is essential for the identification of new lead compounds (e.g., natural products) for vascular therapies.